Potent immunosuppressive effects of the oncometabolite R-2-hydroxyglutarate - Galluzzi, Lorenzo (Oncoimmunology, 2018)
Somatic gain-of-function mutations in isocitrate dehydrogenase (NADP(+)) 1, cytosolic (IDH1) or isocitrate dehydrogenase (NADP(+)) 2, mitochondrial (IDH2) are bona fide oncogenic drivers of acute myeloid leukemia and glioma because the neomorphic enzymes catalyze the synthesis of R-2-hydroxylutarate (R-2-HG), an oncometabolite with robust epigenetic effects. Recent data indicate that R-2-HG released by malignant cells can accumulate in the extracellular space and be taken up by T lymphocytes, ultimately compromising their capacity to mediate anticancer immune responses. Thus, R-2-HG drives oncogenesis and tumor progression not only as a cancer cell-autonomous epigenetic modifier, but also as an immunosuppressive metabolite. Chemical inhibitors of mutant IDH1 and IDH2, which currently are under clinical evaluation, may therefore mediate dual anticancer effects by targeting cancer cells and, at the same time, relieving R-2-HG-mediated immunosuppression.